Estratégias reprodutivas e evolução da fronteira agrícola: um estudo qualitativo para Machadinho dOeste, Rondônia - Juliana Vasconcelos de Souza Barros (2017)
This thesis analyzes the reproductive strategies of two sets of women in the agricultural frontier in the Brazilian Amazon. For reproductive strategy, it is understood that certain reproductive and contraceptive behaviors are adopted, according to the possibilities and adversities offered in the context of the frontier. The objective is to evaluate, within the population dynamics of the frontier, the changes in reproductive and contraceptive strategies throughout the process of evolution within an agricultural frontier region. At the time of the opening of the frontier, there was no solid infrastructure to enable the pioneering generation of women to access sexual and reproductive health services, which are essential for the definition and implementation of reproductive strategies. In addition, the social and economic conditions found initially also may have been reflected in the decisions of these women. In the more advanced stages, the evolution and socioeconomic development of the frontier brought new socioeconomic variables to the context being studied, which can have an influence in the definition of the female reproductive behavior of the new generations. Thus, the different conditions that the evolutionary stages of the frontier offer would make the reproductive strategies different from one another, so that the decisions taken would be different in the initial and the most advanced stages of the frontier. A qualitative study was developed in Machadinho d'Oeste, Rondônia, a municipality that originated from settlement projects to occupy the Brazilian Amazon. 60 in-depth interviews were conducted with women who lived their reproductive period either in the initial or more advanced stages of frontier evolution, creating two comparison groups. The results indicate that there is no direct relationship between land use and number of children, despite what the literature claims. Among women in the first stages, reproductive strategies were defined according to economic constraints and the absence of sexual and reproductive health services; they wanted few children, but they had more than they wanted, because of a lack of knowledge and difficulties in fertility planning. Among women in the more advanced stages of the frontier, the definition of strategies occurs in a different context, but there is also a desire for few children, and they are more successful in implementing preferences. They have greater access to and knowledge about contraception and the motivation for fewer children goes through issues, such as work and schooling. Despite the differences, in both profiles union and childbearing occur at young ages, and there is both a reasonable proportion of pregnancy due contraceptive failure and a high rate of female surgical sterilization.